MORPHOMETRY OF EAGLE SPECIES (FAMILY ACCIPITRIDAE) AT BALI BIRD PARK - Iriani Setyawati; L.P. Eswaryanti Kusuma Yuni; Retno Kawuri; Ni Made Suartini; Ni Wayan Sudatri; I Gede Agus Pradana Putra (Universitas Negeri Manado, 2022)
This study measured the morphometry of raptor species (Family Accipitridae) in Bali Bird Park (BBP) namely Nisaetus cirrhatus (Changeable Hawk Eagle), Elanus caeruleus (Black Winged Kite), Spilornis cheela (Crested Serpent Eagle) and Haliaeetus leucogaster (White Bellied Sea Eagle). Measurements were made with meter tape and caliper on birds that were in their resting period. Raptor at BBP generally rest for 6 months until experience molting before being retrained for 4-5 months, then the birds will be ready to perform bird show for the next 9-12 months. Our measurements obtained the largest bird was Haliaeetus leucogaster with a total body length of 75 cm, wings length 83.5-85 cm, tail length 26 cm, head size (8 cm length and 7 cm width), upper beak (8 cm length and 2.5 cm thick) and lower beak (3 cm length and 1 cm thick), lower limb length (femur 17 cm, tibia 9 cm, metatarsus 11 cm, middle toe 6.5 cm and grip 9 cm). The smallest bird was Elanus caeruleus with a total body length of 33 cm, wing length 39-45 cm, tail length 19 cm, head size (8 cm length, 5.5 cm width), upper beak (2.5 cm length and 0.5 cm thick) and lower beak (1 cm length and 0.3 cm thick), lower limb length (femur 8 cm, tibia 4 cm, metatarsus 5 cm, middle toe 3 cm and grip 5 cm) The morphometry of the species Nisaetus cirrhatus and Spilornis cheela were between the two other bird species.